Penguatan Sistem Pengawasan dalam Penyelenggaran Tahapan Pemilu 2024 - Sumardi Sumardi (Journal of Government Insight, 2022)
This paper aims to find out an analysis of how to build and strengthen the Oversight System in the Implementation of the 2024 Election Stages in Indonesia. The methodology used in this study uses a literature study approach, and data collection is carried out by examining and exploring reputable scientific journals and other supporting documents related to the focus of the study. The results of the study concluded that first, supervision must cover all stages of the election, starting from the preparation, implementation, to the announcement of the results. This will ensure that the electoral process is fair and transparent. Second, the surveillance system must be supported by sophisticated and secure technology. In this case, election organizers need to ensure that their system can detect and prevent cyber manipulation and attacks. Third, the oversight system must include active and involved public participation. This can be achieved by conducting training and providing sufficient information to voters and the general public about the electoral process, as well as providing easy access to election supervisors and observers. Fourth, the role of election supervisors and observers must be recognized and respected by all parties involved in elections. , including election administrators, political parties, and prospective candidates. This will ensure that election supervisors and observers can carry out their duties effectively and without pressure or threats and fifth, an effective monitoring system must be supported by clear and firm rules and laws.